Nitrogen-doped graphene-wrapped Cu2S as a superior anode in sodium-ion batteries. (December 2020) - Cai, Jiyu; Reinhart, Benjamin; Eng, Peter; Liu, Yongqiang; Sun, Cheng-Jun; Zhou, Hua; Ren, Yang; Meng, Xiangbo
Abstract: Sodium-ion batteries (SIBs) have been attracting an ever-growing research interest, mainly ascribed to their cost-effectiveness. However, SIBs have been significantly hindered by lack of a suitable anode. Herein, an exceptional Cu2 S-based composite anode is developed via a facile ball-milling method, in which Cu2 S particles are wrapped by nitrogen-doped graphene sheets (Cu2 S@NG). This Cu2 S@NG composite anode enables extremely long cycling life, ultra-stable cyclability with high capacity, and excellent rate capability. The superior performance of the Cu2 S@NG composite is owing to its intriguing core-shell structure and the exceptional properties of both the Cu2 S and NG. In this study, it is found that the NG shell yields multiple merits in improving the performance of Cu2 S: (i) mitigating the loss of active materials, (ii) constituting a stable interface, (iii) providing improved electrical conductivity and good ionic transfer, and (iv) enhancing mechanical integrity. Additionally, the vital effects of different voltage windows and a surface coating via atomic layer deposition on further enhancing performance are clarified. Significantly, the electrochemical mechanism of Cu2 S during sodiation/desodiation is unveiled using advanced synchrotron-based in-situ X-ray diffraction and X-ray adsorption spectroscopy. This work represents a great advance in seeking high-performance anodes in SIBs. Graphical abstract: A graphene-wrapped Cu2 S composite enables superior performance in sodium storage. Image 1